2010
DOI: 10.1515/bc.2010.128
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to the molecular basics of aryl hydrocarbon receptor biology

Abstract: Depending on their chemical structure and properties, environmental chemicals and other xenobiotics that enter the cell can affect cellular function by either nonselective binding to cellular macromolecules or by interference with cellular receptors, which would initiate a more defined cell biological response. One of these intracellular chemosensor molecules is the aryl hydrocarbon receptor (AhR), a transcription factor of the bHLH/PAS family that is known to mediate the biochemical and toxic effects of dioxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
224
0
17

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(246 citation statements)
references
References 135 publications
5
224
0
17
Order By: Relevance
“…AHR is a highly conserved transcription factor ubiquitously expressed in the brain, whose most potent ligand and activator is 2,3,7,8-tetra-chlorodibenzo-p-dioxin (TCDD), a common industrial pollutant (Abel and Haarmann-Stemmann, 2010). Rodents exposed to TCDD during neurodevelopment exhibit deficits in working memory (Seo et al, 1999), delayed alternation tasks (Markowski et al, 2002), and emotional learning (Nishijo et al, 2007).…”
Section: Aryl Hydrocarbon Receptor Signalingmentioning
confidence: 99%
“…AHR is a highly conserved transcription factor ubiquitously expressed in the brain, whose most potent ligand and activator is 2,3,7,8-tetra-chlorodibenzo-p-dioxin (TCDD), a common industrial pollutant (Abel and Haarmann-Stemmann, 2010). Rodents exposed to TCDD during neurodevelopment exhibit deficits in working memory (Seo et al, 1999), delayed alternation tasks (Markowski et al, 2002), and emotional learning (Nishijo et al, 2007).…”
Section: Aryl Hydrocarbon Receptor Signalingmentioning
confidence: 99%
“…6 We have previously shown that UVB exposure of keratinocyte (KC) resulted in the activation of the aryl hydrocarbon receptor (AHR), 10 a ligand-activated transcription factor and central regulator of drug metabolism. 11 More precisely, UVB rays are absorbed by free tryptophan in the cytosol of KC, resulting in the formation of the tryptophan-photoproduct 6-formylindolo [3,2-b]carbazole (FICZ), 10 a high-affinity ligand of the AHR. 12 Alike polycyclic aromatic hydrocarbons (PAHs) and dioxins, FICZ binds to the AHR and initiates the dissociation of the cytosolic AHR multiprotein complex, consisting of heat-shock protein 90, tyrosine kinase c-src, and other co-chaperones, thereby enabling the nuclear translocation of AHR.…”
mentioning
confidence: 99%
“…12 Alike polycyclic aromatic hydrocarbons (PAHs) and dioxins, FICZ binds to the AHR and initiates the dissociation of the cytosolic AHR multiprotein complex, consisting of heat-shock protein 90, tyrosine kinase c-src, and other co-chaperones, thereby enabling the nuclear translocation of AHR. 10,11 In the nucleus, the AHR dimerizes with ARNT (AHR nuclear translocator) and binds to xenobiotic-responsive elements (XRE) in the promoter region of genes to enforce their transcription. The AHR gene battery encodes for drug-metabolizing enzymes, such as cytochrome P450 (CYP) 1A1, as well as for proteins involved in the regulation of cell growth and differentiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their binding will prevent the negative impact of AhR signaling in response to pollution. These AhR antagonist belongs mainly to polyphenol class such as flavonoids or catechins [36,37].…”
Section: Activation Of the Aryl Hydrocarbon Receptor (Ahr)mentioning
confidence: 99%